Generation and application of four-wave mixing in collinear high harmonic generation - Dinh, Khuong Ba; Tran, Khoa Anh; Chau, Thong Huy; Truong, Vi Khanh; Nguyen, Hoi Ba; Nguyen, Hung Tan; Ho, Tien Phuoc; Dao, Lap Van (Communications in Physics, 2023)
We describe a thorough study of the wave-mixing procedure in the extreme ultraviolet (XUV) region involving three laser fields (800 nm, 1400 nm and 1860 nm). In addition to the phase matched HHG spectrum generated by an 800-nm laser (driving field), non-integer order wave-mixing spectra are produced when the driving field and the control field (1400 nm or 1860 nm) are collinearly focused into krypton gas. In addition, the simultaneous presence of three laser fields generates resolvable four-wave mixing (FWM) frequencies that clearly indicate the contribution of each control field. We also discuss an application of the FWM scheme to extend the HHG cutoff region and generate the XUV quasi-continuum spectrum.